STRATEGIES OF TEACHERS GRADUATED FROM SALAF ISLAMIC BOARDING SCHOOL IN IMPLEMENTING ISLAMIC VALUES IN PUBLIC EDUCATIONAL INSTITUTIONS - Moh. Mohlas; Hasan Baharun (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This study aims to analyze the strategies of teachers from traditional Islamic boarding schools (pesantren) in implementing Islamic values in public educational institutions. The main focus of this study is how teachers from Islamic boarding schools are able to instill Islamic values in educational environments that are not entirely based on religion. The research method used was a qualitative case study approach. Data were obtained through in-depth interviews, observation, and documentation of teachers from Islamic boarding schools who teach in public schools. The results show that the strategies used include integrating Islamic values into learning, exemplary behavior, instilling Islamic morals, and a personal approach to students. Teachers from Islamic boarding schools play a crucial role as moral and spiritual agents in a heterogeneous school environment. The implications of this study indicate that the religious competence and character of Islamic boarding school teachers can strengthen character education in public institutions and serve as models for the application of religious moderation in educational practice. This study recommends collaborative training between public institutions and Islamic boarding schools to enrich inclusive and contextual Islamic values-based educational strategies.